"I want to see them thrive!": exploring health service research priorities for young Aboriginal children growing up in Alice Springs - a qualitative study - C. Lloyd-Johnsen; A. Hampton; E. Stubbs; S. Moore; S. Eades; A. D'Aprano; S. Goldfeld (BMC, 2024)
Abstract To better understand the specific influences of early life on the long-term health and well-being of local Aboriginal children in Alice Springs, high-quality local longitudinal data is required. The Central Australian Aboriginal Congress and the Murdoch Children's Research Institute are exploring the feasibility of establishing a cohort study to fill this gap. A nested qualitative study was conducted to identify priority issues that can be translated into research questions answerable through the proposed cohort study. Semi-structured interviews and focus group discussions (FGDs) were conducted with a range of key community stakeholders, parents and caregivers of young Aboriginal children from Alice Springs in the Northern Territory between 2020 and 2021. Two Aboriginal and two non-Aboriginal researchers conducted 27 interviews and 3 FGDs with 42 participants. Three broad themes were constructed through reflexive thematic analysis representing the areas of focus community stakeholders and parents want future research to prioritise: (1) social determinants of health (2) building positive connections, and (3) making sure kids grow up strong and healthy. Priority setting for future research should be driven by Aboriginal and Torres Strait Islander peoples in order to be of practical benefit to their community. This qualitative study found that housing, transport and positive connections through nurturing and engaged parents were some of the most important issues raised. Participants also wanted future research to focus on issues specific to children such as nutrition, hearing loss, language development and capacity to learn. These findings will guide future work led by local Aboriginal researchers to co-design the proposed cohort study.